Effects of leg strength, coordination, and balance on futsal passing among high school students - Bismil Fattullah; Arsil Arsil; Atradinal Atradinal; Vega Soniawan (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study examined the relationships among leg muscle strength, lower limb coordination, balance, and futsal passing ability in high school athletes. A quantitative correlational design was employed involving 30 futsal athletes from SMAN 2 Kota Solok selected through total sampling. Data were collected using standardized tests of leg muscle strength, lower limb coordination, balance, and passing ability. Path analysis was applied at a significance level of 0.05. Leg muscle strength, lower limb coordination, and balance were significantly associated with passing ability. Balance showed the strongest direct contribution and significantly mediated the relationships between leg muscle strength, lower limb coordination, and passing ability. Simultaneously, the three variables explained 97% of the variance in passing performance. Futsal passing ability is closely related to the integration of physical and coordinative components, particularly balance. Therefore, training programs should simultaneously develop strength, coordination, and balance to improve passing performance among high school futsal athletes.